Tax revolts: an international perspective - Tinotenda, Tariro Chizanga (Rhodes University, Faculty of Commerce, Department of Accounting, 2020)
The main goal of this study is to investigate whether tax revolts currently taking place and apparently threatening to take place in South Africa follow patterns shown in past international tax revolts or follow a unique pattern of their own. Tax revolts or tax rebellions are not a new phenomenon; they can be traced back to the beginning of time. Renowned tax revolts of the past include the Magna Carta and the Peasants' Revolt in England, the Boston Tea Party, the Whiskey Rebellion, the Zimbabwean poll tax revolt, the Bambatha rebellion, the Tigre Rebellion, Proposition 13 and Margaret Thatcher's poll tax revolt. These tax revolts were usually caused by the high burden of taxation, excessive government expenditure, corruption of government officials, declining tax morale of taxpayers and taxpayers' perceptions of unfairness. In South Africa, elements of tax revolts have been on the rise. There has been a tax revolt against the e-tolling system in Gauteng since 2013. Non-payment of municipal rates is another form of tax revolt that has been and is happening in South Africa. Trade unions have also threatened strikes and mass action against various tax changes, including the value-added tax increase. Taxpayers, through media reporting, have been witnessing an increase in the use of taxpayers' money for non-governmental agendas or overstated budgets. An increasing number of South Africans have been emigrating financially from South Africa to avoid a high taxation burden. The study falls within a post-positivist paradigm and an interpretive methodology is applied in the present research. The methodology is based on the fact that the social reality of tax revolts is not singular or objective, instead it is influenced by human experiences and social contexts. The study finds that tax revolts are currently occurring and threatening to occur in South Africa. The patterns of South African tax revolts are to a great extent similar to the patterns of international tax revolts, indicating the universalism of tax revolts. The study also confirms that South African tax revolts are, to a certain extent, unique.
Keywords: Taxation -- Public opinion; Taxation -- Law and legislation -- South Africa; Income tax -- South Africa; South Africa -- Economic conditions; Fiscal policy -- South Africa